Time management - Taylor, Trevor; Grant, Felicity; Kingsland, Paddy (London : Taylor Made Film, 1992)
The video'shows how to creat time to think and how to feel in control of your life. Catologue
Contents: part 1 - Discussion and case study; part 2 - Lampeter & Son
Executive producer, Trevor Taylor; music composer, Paddy Kingsland
Keywords: Time management